A Multichannel Cross-Layer Architecture for Multimedia Sensor Networks. (31st March 2013) - Çevik, Taner; Zaim, Abdül Halim
Abstract : Depending upon the technological developments, the same fast evolution has occurred in the structures of sensor networks, their composing devices which are sensor nodes, and their application areas. Those tiny, energy-constrained, mostly non-real-time data transmitting sensor nodes have evolved to more energy-containing, camera-adapted, real-time multimedia-data-transmitting devices. Developments in the usage areas and the capabilities have revealed some other problems such as time limited data transmission. In this paper, we propose a multichannel cross-layer architecture for Quality of Service (QoS) constrained multimedia sensor networks. The proposed architecture considers both the time and energy efficiency concepts. Energy efficiency is succeeded by ensuring the fair load distribution among the nodes during a real-time multimedia packet stream transmission. Besides ensuring the fair load distribution, on-time packet transmission is also assured by constructing the paths with a hard reservation technique depending on the predetermined QoS constraints. Simulations show that the proposed architecture provides higher performance than the Greedy approach and the LEERA scheme.